Pengaruh Religiusitas dan Persepsi Masyarakat terhadap Minat Menabung di Bank Syariah - Rafi Irsyad; Pranoto Effendi; Muhammad Isman Almaududi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was conducted to determine the influence of religiosity and public perception on interest in saving at sharia banks with a sample of respondents from the Rukun Warga 06 West Cilandak community. This study uses a quantitative approach. The results of the analysis show that the level of religiosity and public perception have a positive and significant influence on interest in saving. So these two variables are believed to increase interest in saving at sharia banks, therefore to increase the number of customers of a sharia bank it is necessary to increase outreach programs to the public so that their understanding and knowledge increases regarding the products and characteristics of sharia banks which are different from conventional banks.